A small nucleolar RNA, SNORD126, promotes adipogenesis in cells and rats by activating the PI3K–AKT pathway. Issue 4 (22nd September 2020) - He, Yi; Wu, Yu; Mei, Bin; Fang, Xianlong; Cai, Guangzhen; Cai, Ning; Wu, Qiqi; Huang, Zhao; Ge, Chang; Liang, Huifang; Zhang, Bixiang; Chen, Xiaoping; et al.
Abstract: Small nucleolar RNA (snoRNA) plays important role in various histogenesis. Whether snoRNA plays a role in adipogenesis is unknown. SNORD126 is a C/D box snoRNA. We previously demonstrated that SNORD126 promoted hepatocellular carcinoma cell growth by activating the phosphoinositide 3‐kinase–protein kinase B (Akt) pathway through upregulating fibroblast growth factor receptor 2 expression. In the present study, we found that the expression of SNORD126 was downregulated in the obesity‐related tissues in high‐fat diet‐fed rats. Overexpression of SNORD126 in 3T3‐L1 cells promoted adipocytes differentiation. SNORD126 significantly increased the expression of CCAAT/enhancer‐binding protein α, fatty acid‐binding protein 4, peroxisome proliferative‐activated receptor‐γ, and the phosphorylation of Akt and p70S6K. Overexpression of SNORD126 in human adipose‐derived stem cells stimulated adipogenesis and increased phosphorylation of Akt. Meanwhile, SNORD126 increased the messenger RNA and protein levels of cyclin D1 and cyclin‐dependent kinase 2, which promoted mitotic clonal expansion progression during the early stage of 3T3‐L1 cell differentiation. We further found that SNORD126 accelerated the growth of the groin fat pad and increased phosphorylation of Akt and p70S6K in rats. Overall, our results suggested that SNORD126 promoted adipocyte differentiation through increasing phosphorylation of Akt and p70S6K both in vitro and in vivo. Abstract : SNORD126 promoted adipogenesis in 3T3‐L1 cells and human adipose‐derived stem cells through increasing phosphorylation of protein kinase B (Akt) and p70S6K. SNORD126 accelerated the growth of the inguinal fat pad in rats.